Pengaruh Terapi Murottal Surat Arrahman terhadap Kecemasan pada Pasien Pre Op Laparoscopy di Semarang - Cita Setya Utami; Wahyu Endang Setyowati; Dwi Heppy Rochmawati (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Surgical procedures, including laparoscopic surgery, may cause preoperative anxiety arising from fear of the surgery process, uncertain outcomes, and postoperative pain. This anxiety can affect anesthesia and recovery aspects. The purpose of this study was to determine the effect of Murottal recitation of Surah Ar-Rahman on anxiety in preoperative laparoscopy patients. This study employed a quasi-experimental design with a pretest–posttest control group. A total of 40 respondents were recruited using total sampling. Data were collected through questionnaires. Data analysis was conducted using the Wilcoxon test for within-group differences and the Mann-Whitney test for between-group differences. The majority of respondents in both intervention and control groups were late elderly, employed, male, and had no history of illness. Before therapy, anxiety levels in both groups were predominantly moderate. After therapy, most respondents in the intervention group experienced mild anxiety, whereas in the control group most remained in the moderate category. Statistical analysis showed a significant effect of Murottal recitation of Surah Ar-Rahman on reducing anxiety, both in the intervention group (Z = -5,477; p = 0.000) and the control group (Z = -2.000; p = 0.046). Overall, Murottal recitation of Surah Ar-Rahman was proven to be significantly effective in reducing respondents’ anxiety levels (Z = -4,534; p = 0.000). It is recommended that families play an active role in supporting anxiety reduction in patients undergoing surgery, for example, by suggesting or facilitating the patients to listen to Murottal recitation of Surah Ar-Rahman.